2018
DOI: 10.1186/s12888-018-1659-1
|View full text |Cite
|
Sign up to set email alerts
|

Work-related adverse events leaving their mark: a cross-sectional study among Dutch gynecologists

Abstract: BackgroundHealth care professionals who are frequently coping with traumatic events have an increased risk of developing a posttraumatic stress disorder. Research among physicians is scarce, and obstetrician-gynecologists may have a higher risk. Work-related traumatic events and posttraumatic stress disorder among obstetricians-gynecologists and the (desired) type of support were studied.MethodsA questionnaire was emailed to all members of the Dutch Society of Obstetrics and Gynaecology, which included residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 38 publications
(25 reference statements)
3
58
0
3
Order By: Relevance
“…Whether the non-practicing group stopped working because of complaints at the disciplinary board cannot be answered because of the small numbers. The amount pediatricians who received a complaint to the disciplinary board is low compared to gynecologists [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the non-practicing group stopped working because of complaints at the disciplinary board cannot be answered because of the small numbers. The amount pediatricians who received a complaint to the disciplinary board is low compared to gynecologists [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…When physicians are unfit, this may have a negative impact on their practice [ 23 ], whereas occupational well-being can positively contribute to patient satisfaction and the quality of interpersonal aspects of care [ 6 ]. In this questionnaire, coping strategies applied by the pediatricians were similar to coping strategies of gynecologists in the study by Baas et al [ 17 ]. Almost 20% of the respondents adjusted their job and 40% seriously considered quitting their job completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey by the General Medical Council reported that 24% of trainees and 21% of trainers from across the United Kingdom (UK) described ‘feeling burnt out’ based on self-reported symptoms 9. The consequences of burnout among doctors have been investigated primarily in the United States (USA)10 with relatively few large studies conducted in Europe11–16 and Asia17 18 to validate these findings internationally. These include a negative impact on health including higher rates of substance abuse, depression, suicide and a poorer quality of life 19 20.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of midwives can be distinguished: midwives working in primary care, who independently assist women at home and in birthing centers, and midwives working in secondary or tertiary care, who work in a hospital setting under supervision of an obstetrician. Recently, a study from the Netherlands on the impact of work‐related adverse events on gynecologists and residents in obstetrics and gynecology was published . However, no data on midwives and possible associations between psychological symptoms and the organization of care are available.…”
Section: Introductionmentioning
confidence: 99%